An informational support programme within the context of health psychology and its impact on aspects of psychological functioning of parents of children with cystic fybrosis - Marshall, Jerome (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA) -- University of Stellenbosch, 2006.